Evaluation of Tehran Province Livestock Production from Water Footprint Prospective - Ali Mohammadi; Hossein Yousefi; Ali Mahmoudi Aznaveh (Environmental Energy and Economic Research)
In Tehran, Iran's most populous province, there has been a notable surge in livestock production in recent years, prompting a critical examination of water resource allocation through the water footprint indicator. This study uniquely concentrates on livestock productions at a provincial level, specifically within four key counties boasting the highest production rates in Tehran province. Employing the methodology introduced by Mekonnen and Hoekstra (2012), a comprehensive analysis of the water footprints (WFs) associated with various livestock productions is conducted. The results underscore that milk production holds the highest average water footprint at 13,007 cubic meters per ton, significantly surpassing other products. Conversely, lamb exhibits the lowest water footprint at 2,266.7 cubic meters per ton among livestock productions. Evaluation of fresh water sources in relation to animal water footprints highlights unsustainable conditions in southern counties, particularly Islamshahr, due to a pronounced disparity between their product water footprint and available water resources. In contrast, northern counties demonstrate lower water footprints, aligning with their abundant water resources. A scrutiny of water resources reveals vulnerability in Tehran's dams, approaching long-term minimum water volume despite the escalating levels of livestock production. While Varamin features a wastewater treatment unit contributing substantial volume (160 million cubic meters) and recycled water to the system, wells and Qanats play a role in water provision but prove inadequate. Given the substantial productions and water resource scarcity, a recommendation is made to discontinue all livestock production; however, if production persists, focusing solely on sheep meat (lamb) in northern counties is deemed a feasible strategy.